Analisis Pendapatan Biji Kakao di Kecamatan Way Lima Kabupaten Pesawaran - Irawati, Luluk; Oktaviani, Anggita Dwi; Zaini, Muhammad; Marbudi, Marbudi; Ulfah, Maria (Universitas Galuh, 2026)
The purpose of this research to analyze cocoa farming income based on three post-harvest treatments, namely wet, non-fermented, and fermented cocoa beans in Way Lima District, Pesawaran Regency. The research method used a survey with a purposive sampling technique on 30 cocoa farmers. Data were analyzed using a financial income approach and business feasibility through the Benefit Cost (B/C) ratio. The results showed that post-harvest treatments made a significant difference to farmers' income and revenue. The highest income was obtained from fermented cocoa at IDR 57,500,000/hectare/year, followed by non-fermented at IDR 52,542,320.56/hectare/year, and wet cocoa beans at IDR 27,864,192.73/year. The income from fermented cocoa farming is Rp 44,602,761.09/year, higher than non-fermented cocoa at Rp 40,267,179.96/hectare/year and wet beans at Rp 18,435,394.09/hectare/year. The B/C ratio value shows that all post-harvest cocoa treatments are feasible to be cultivated (B/C > 1), with the highest value in fermented cocoa (3.35), then non-fermented cocoa (3.28), and wet cocoa beans (1.96). These results explain that fermented cocoa provides added value, improved quality, and higher income for cocoa farmers, although it requires additional costs and labor. Therefore, the application of fermentation needs to be continuously encouraged as a strategy to improve the welfare of cocoa farmers.